Altered Resting Brain Functions in Patients With Irritable Bowel Syndrome: A Systematic Review - Yu, Zheng; Liu, Li-Ying; Lai, Yuan-Yuan; Tian, Zi-Lei; Yang, Lu; Zhang, Qi; Liang, Fan-Rong; Yu, Si-Yi; Zheng, Qian-Hua (Frontiers in Human Neuroscience, 2022)
Background The neural activity of IBS patients in the resting state fMRI been systematically studied. The purpose of this study was to compare the resting-state brain functions of IBS patients with healthy controls (HCs). Methods The published neuroimage studies were obtained from electronic databases including PubMed, EMBASE, PsycINFO, Web of Science Core, CNKI Database, Wanfang Database, VIP Database, CBMdisc. Search dates were from inception to March 14th, 2022. The studies were identified by the preidentified inclusion and exclusion criteria. Two independent reviewers compiled the studies and evaluated them for quality and bias. Results Altogether 22 fMRI studies were included in this review. The risk of bias of the included studies was generally low. The findings indicated that in IBS patients, increased or decreased brain areas were mostly associated with visceral sensations, emotional processing, and pain processing. According to brain network research, IBS may exhibit anomalies in the DMN, CEN, and emotional arousal networks. The fluctuations in emotion (anxiety, sadness) and symptoms in IBS patients were associated with alterations in the relevant brain regions. Conclusion In the present systematic evaluation, patients with IBS had physiopathological spontaneous brain function abnormalities, which were whole-brain distribution and lack of validation. More research is required to accurately distinguish the distinct resting-state neurological characteristics of IBS.